Development of 1-mile walk tests to estimate aerobic fitness in children. Issue 2 (3rd April 2018) - Sung, Hoyong; Collier, David N.; DuBose, Katrina D.; Kemble, C. David; Mahar, Matthew T.
ABSTRACT: To examine the reliability and validity of 1-mile walk tests for estimation of aerobic fitness (VO2max ) in 10- to 13-year-old children and to cross-validate previously published equations. Participants ( n  = 61) walked 1-mile on two different days. Self-reported physical activity, demographic variables, and aerobic fitness were used in multiple regression analyses. Eight models were developed with various combinations of predictors. The recommended model for fitness testing in schools was: VO2max  = 120.702 + (4.114 × Sex [F = 0, M = 1]) – (2.918 × 1-mile Walk Time [min]) – (2.841 × Age), R  = .73, standard error of estimate = 6.36 mL·kg −1 ·min −1 . Cross-validation of previously published equations demonstrated lower correlations with measured VO2max than the newly developed walk tests. Evidence of reliability and validity for 1-mile walk tests to estimate VO2max in young children was provided. The model that included 1-mile walk time, age, and sex may be appropriate for youth fitness testing in physical education, particularly for unmotivated or overweight young children.